Optimalisasi Lembaga Farmasi TNI AL Dalam Produksi Sediaan Farmasi Guna Mendukung Ketahanan Kesehatan - Ruskar, Dandung; Kumala, Shirly; Noor, Laili Savitri (PendIPA Journal of Science Education, 2025)
RIPIN (National Industrial Development Master Plan) 2015-2035 has placed the Pharmaceutical Industry as one of the priority industries to be developed. Meanwhile, the results of the ASEAN Summit in September 2023 held in Jakarta stated that Indonesia had the lowest score for indicators of drug availability and costs, which was 54.02. The existence of BPJS Kesehatan in 2014 greatly reduced the role and function of the Navy Pharmaceutical Institution as the pharmaceutical industry owned by the TNI AL. Currently, Lafial only produces pharmaceutical preparations for health support whose need is very limited because the state budget received is also reduced. In order to support and increase the availability of medicines in Indonesia, the role and function of Lafial should be utilized. The purpose of this study was to design the right business strategy for Lafial to meet the needs of national medicines while reducing dependence on the state budget through SWOT analysis and QSPM matrix. This was qualitative research using a descriptive analysis approach to further explore the internal and external parameters factors of Lafial. The data collection technique used was triangulation from in-depth interviews and FGDs on key personnel pharmacists as well as questionnaires through Google Forms for all pharmacists outside key personnel and secondary data collection. The results of the study on the strength component score was 2.022; the weakness component was 1.540; the opportunity component was 2.020 and the threat component was 1.673. With these results, Lafial's position is in cell number I of the IE matrix and quadrant I of the SWOT quadrant. The strategy analysis using QSPM provides that the strategy of sharpening market penetration through coordination with the Officials and Heads of the Navy health facilities to use Lafial's finished products has the highest TAS value with a value of 5,611. Then the strategy of developing the market through coordination with the Ministry of Health and the Ministry of Finance to be able to produce and deposit PNBP has a TAS value of 5.204. The last strategy is a strategy to increase operational efficiency through coordination with the state-owned and private pharmaceutical industry through drug toll manufacturing activities with a TAS value of 4.332.